3D-Printed Microneedles Create Precise Perforations in Human Round Window Membrane in Situ. Issue 2 (February 2020) - Chiang, Harry; Yu, Michelle; Aksit, Aykut; Wang, Wenbin; Stern-Shavit, Sagit; Kysar, Jeffrey W.; Lalwani, Anil K.
Abstract : Hypothesis: Three-dimensional (3D)-printed microneedles can create precise holes on the scale of micrometers in the human round window membrane (HRWM). Background: An intact round window membrane is a barrier to delivery of therapeutic and diagnostic agents into the inner ear. Microperforation of the guinea pig round window membrane has been shown to overcome this barrier by enhancing diffusion 35-fold. In humans, the challenge is to design a microneedle that can precisely perforate the thicker HRWM without damage. Methods: Based on the thickness and mechanical properties of the HRWM, two microneedle designs were 3D-printed to perforate the HRWM from fresh frozen temporal bones in situ (n = 18 total perforations), simultaneously measuring force and displacement. Perforations were analyzed using confocal microscopy; microneedles were examined for deformity using scanning electron microscopy. Results: HRWM thickness was determined to be 60.1 ± 14.6 (SD) μm. Microneedles separated the collagen fibers and created slit-shaped perforations with the major axis equal to the microneedle shaft diameter. Microneedles needed to be displaced only minimally after making initial contact with the RWM to create a complete perforation, thus avoiding damage to intracochlear structures. The microneedles were durable and intact after use. Conclusion: 3D-printed microneedles can create precise perforations in the HRWM without damaging intracochlear structures. As such, they have many potential applications ranging from aspiration of cochlear fluids using a lumenized needle for diagnosis and creating portals for therapeutic delivery into the inner ear. Abstract : Supplemental Digital Content is available in the text